A highly wear-resistant self-cleaning ecological permeable brick and its preparation method
By using aggregates combining micro-nano dual-scale corundum particles and WC, combined with spray granulation method and high-temperature heat treatment technology, permeable bricks with high wear resistance, self-cleaning and water permeability are prepared, solving the problems of existing permeable bricks. Solving the problem of insufficient performance, it achieves higher comprehensive performance and environmental significance.
Patent Information
- Application Number
- CN202410873567.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-07-01
AI Technical Summary
Existing permeable bricks have insufficient performance in terms of wear resistance, self-cleaning and permeability, making it difficult to meet the needs of urban drainage and environmental protection.
Using aggregates combining micro-nano dual-scale corundum particles and WC, permeable bricks are prepared through spray granulation and high-temperature heat treatment, and a TiO2 layer imitating a lotus leaf structure is designed on the surface.
It significantly improves the wear resistance, self-cleaning and water permeability of permeable bricks, extends its service life, reduces environmental pollution, and is suitable for urban construction and environmental protection.
Smart Images

Figure CN118812245B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of permeable bricks, and in particular to a highly wear-resistant and self-cleaning ecological permeable brick and a preparation method thereof. Background Art
[0002] With the acceleration of urbanization, cities are facing many challenges, one of which is the problem of poor rainwater drainage and environmental pollution caused by the hardening of urban ground. Traditional hardened ground materials such as concrete and stone, although strong and durable, lack water permeability, resulting in the inability of rainwater to penetrate quickly, increasing the risk of urban waterlogging. At the same time, dust and dirt are easily accumulated on the surface of these materials, which not only affects the appearance, but may also cause secondary pollution. Against this background, highly wear-resistant and self-cleaning ecological permeable bricks came into being. This new type of environmentally friendly building material not only has the strong and durable characteristics of traditional building materials, but more importantly, it has good water permeability and self-cleaning functions. While ensuring the beauty and practicality of the ground, it can effectively alleviate the pressure of urban drainage, reduce environmental pollution, and create a more comfortable and healthy living environment for urban residents. Therefore, highly wear-resistant and self-cleaning ecological permeable bricks have broad application prospects in urban construction, garden landscape, municipal engineering and other fields.
[0003] Although ecological permeable bricks have made significant progress in recent years, and their design and application have made breakthroughs, there are still many aspects that need to be improved. The primary problem is the lack of wear resistance, which is mainly due to the relatively fragile materials used in traditional ecological permeable bricks, which are difficult to effectively resist the friction and impact of the external environment. At the same time, the hardness and structural design of the materials have not reached the ideal wear resistance standard. Secondly, the defects in self-cleaning performance cannot be ignored. This is mainly due to the roughness of the brick surface and the special pore structure, which makes it easy for dirt to accumulate. In addition, the material is not hydrophilic enough, making it difficult to effectively remove dirt. In the manufacturing process of permeable bricks, the self-cleaning performance needs to be improved. Furthermore, insufficient permeability is also a significant problem, which is mainly attributed to the unreasonable pore structure and channel design of permeable bricks, as well as the limitations of the permeability of the material itself. Therefore, in order to overcome these challenges, it is urgent to develop a new type of permeable brick, which not only needs to have high wear resistance and be able to maintain long-term durability in various harsh environments, but also needs to have excellent self-cleaning properties to ensure the cleanliness and beauty of the surface, and at the same time, it must have excellent permeability to cope with the pressure of the urban drainage system. Only in this way can the market's urgent demand for high-performance permeable bricks be met and the sustainable development of urban construction be promoted. Summary of the invention
[0004] (1) Technical issues solved
[0005] The purpose of the present invention is to provide a highly wear-resistant and self-cleaning ecological permeable brick and a preparation method thereof, so as to solve the problem that the current permeable bricks are insufficient in wear resistance, self-cleaning and permeability.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A highly wear-resistant, self-sealable ecological permeable brick is made of the following components in parts by weight: 60 to 95 parts of aggregate, 4 to 9 parts of sintering aid, 2 to 4 parts of sodium dodecyl sulfate, 5 to 10 parts of water and 21 to 43 parts of titanium-containing precursor solution;
[0009] The aggregate is spherical and consists of micro-nano dual-scale corundum particles and WC phase;
[0010] The micro-nano dual-scale corundum particles are composed of micron-scale corundum particles with a particle size of 4 to 45 μm and nano-scale corundum particles with a particle size of 30 to 90 nm;
[0011] The titanium-containing precursor solution is prepared from the following components in parts by weight: 4 to 9 parts of tetrabutyl titanate, 8 to 12 parts of anhydrous ethanol, 3 to 8 parts of acetic acid, 3 to 6 parts of polyvinyl alcohol and 3 to 8 parts of water;
[0012] The WC phase is formed in situ at high temperature after the WC precursor solution is dried;
[0013] The WC precursor solution is prepared from the following components in parts by weight: 20 to 45 parts of ammonium tungstate hydrate, 8 to 15 parts of glucose, 2 to 4 parts of sodium dodecylbenzene sulfonate and 30 to 45 parts of water;
[0014] The interface between the micro-nano dual-scale corundum particles and the WC phase contains a coherent interface;
[0015] The sintering aid is a mixture of SiO2 and bentonite, and the mass ratio of SiO2 to bentonite is 1:(1-3);
[0016] The porous surface inside the highly wear-resistant self-cleaning ecological permeable brick has a TiO2 layer with a lotus leaf structure;
[0017] The TiO2 layer is synthesized at high temperature after the titanium precursor solution is dried;
[0018] The particle size of the aggregate is 2 to 10 mm;
[0019] The volume percentage of the micron-scale corundum particles and the nano-scale corundum particles is (75-85%):
[0020] (15-25%);
[0021] The volume percentage of the micro-nano dual-scale corundum particles and the WC phase is (55-75%): (25-45%). The present invention also provides a method for preparing a highly wear-resistant and self-cleaning ecological permeable brick, which comprises the following steps:
[0022] S1: preparing corundum particles: crushing, ball milling and screening the waste corundum ceramics in sequence to screen out micron-scale corundum particles with a particle size of 4 to 45 μm and nano-scale corundum particles with a particle size of 30 to 90 nm for use;
[0023] S2: Preparation of WC precursor: by weight, 20 to 45 parts of ammonium tungstate hydrate, 8 to 15 parts of glucose, 4 to 8 parts of sodium dodecylbenzene sulfonate and 30 to 45 parts of water are mixed evenly.
[0024] S3: preparing aggregate: by weight, 40 to 65 parts of the micro-nano dual-scale corundum particles obtained in S1, 20 to 45 parts of the WC precursor solution obtained in S2 and 3 to 8 parts of polyvinyl alcohol are mixed evenly to prepare a ceramic slurry, and then the aggregate blank is obtained by spray granulation, which is then heat-treated at a high temperature to obtain the aggregate.
[0025] S4: Initial sintering of permeable bricks: 60-95 parts of aggregate, 4-9 parts of sintering aid, 2-4 parts of sodium dodecyl sulfate and 5-10 parts of water are mixed evenly, put into a mold and pressed to obtain a permeable brick blank. After drying, the initial sintering is carried out to obtain a pre-finished permeable brick.
[0026] S5: Prepare a titanium-containing precursor solution for impregnation: mix 4 to 9 parts of tetrabutyl titanate and 8 to 12 parts of anhydrous ethanol to obtain a solution A for use, then mix 3 to 8 parts of acetic acid and 3 to 8 parts of water to obtain a solution B, and then drip the solution B into the solution A drop by drop to obtain a titanium-containing precursor solution for impregnation.
[0027] S6: Secondary sintering of permeable bricks: The permeable brick pre-finished product prepared in S4 is completely immersed in the titanium-containing precursor solution prepared in S5. After immersion for 5 to 10 minutes, the permeable brick pre-finished product is taken out and dried, and then subjected to secondary sintering to finally obtain a highly wear-resistant and self-cleaning ecological permeable brick.
[0028] Furthermore, the parameters of the spray granulation method in step S3 are: the centrifugal frequency of the atomizing disk is 25-35, the inlet air temperature is 160-210° C., the outlet air temperature is 85-100° C., and the slurry inlet pressure is 40-60.
[0029] Furthermore, the parameters of the heat treatment in step S3 are: heat treatment is performed in an argon atmosphere, the heat treatment temperature is 900-1000° C., and the heat treatment time is 1-3 hours.
[0030] Furthermore, the parameters of the initial sintering in step S4 are: sintering temperature of 1100-1250° C. and sintering time of 4-8 hours in normal pressure and air atmosphere.
[0031] Furthermore, the parameters of the secondary sintering in step S6 are: under normal pressure and in a nitrogen atmosphere, the sintering temperature is 500-600° C., and the sintering time is 2-5 hours.
[0032] The present invention uses waste corundum to obtain corundum particles through crushing, ball milling and screening, which has the following multiple effects: First, in terms of resource utilization, the reuse of waste corundum greatly saves the demand for new materials, reduces energy consumption and raw material consumption, and realizes the effective utilization of resources. Secondly, from the perspective of environmental protection and emission reduction, the implementation of this method significantly reduces the pollution to the environment, avoids the environmental damage caused by the mining and processing of natural corundum ore, and shows a strong environmental awareness. Furthermore, the use of waste corundum also reduces material costs and improves the market competitiveness of products. In addition, the treated corundum particles have good water permeability, so that permeable bricks can more effectively reduce urban rainwater runoff, improve urban drainage systems, and prevent the occurrence of floods. Finally, the high hardness and wear resistance of corundum particles improve the strength and durability of permeable bricks, so that they can withstand the pressure of vehicles and pedestrians for a long time, and extend the service life. In summary, the present invention not only realizes the reuse of waste resources, reduces environmental pollution, but also improves the performance and economic benefits of permeable bricks, and has far-reaching environmental significance and market prospects.
[0033] The present invention adopts a micro-nano dual-scale corundum particle design with the following multiple effects: at the micro-nano dual-scale level, the micro-scale corundum particles provide the basic strength and stability of the permeable brick, while the nano-scale particles fill the gaps between the micro-scale particles, enhancing the interface bonding, thereby significantly improving the strength and wear resistance of the permeable brick. This dual-scale design enables the permeable brick to disperse and resist stress more effectively when subjected to external forces, thereby extending the service life. At the same time, through a reasonable particle assembly design, that is, corundum particles of different sizes and shapes are mixed in a certain proportion, a tight stacking structure is formed, which significantly increases the density of the permeable brick, improves the overall performance of the permeable brick, such as compressive strength, flexural strength and freeze-thaw resistance, so that it can adapt to a more complex and changeable environment. Therefore, the permeable brick of the present invention not only realizes the recycling of resources and reduces environmental pollution, but also has higher strength and wear resistance, as well as better density and overall performance, making a positive contribution to urban construction and environmental protection.
[0034] The present invention adopts micro-nano dual-scale corundum particles and WC to prepare aggregates, which has the following multiple effects: first, through the use of micro-nano dual-scale corundum particles, the permeable bricks are strengthened at both micro and nano scales, providing basic strength and stability for the brick body. At the same time, the added WC is closely combined with the corundum particles through in-situ synthesis technology to form a strong binding force. This in-situ synthesis between WC and corundum particles not only increases the bonding strength between aggregate particles, but also forms a coherent interface between WC and corundum particles. The existence of the coherent interface means that the crystal structures of WC and corundum particles can match each other, so that the atoms between the interfaces can be closely arranged, thereby greatly enhancing the interface bonding strength. This enhanced interface bonding force enables the permeable brick to disperse and resist stress more effectively when subjected to external forces, thereby improving the strength and wear resistance of the permeable brick. In addition, as a material with high hardness and high wear resistance, the addition of WC further improves the wear resistance of the permeable brick. This allows the permeable brick to maintain a longer service life when subjected to frequent friction between vehicles and pedestrians, reducing the frequency of maintenance and replacement. In summary, the present invention adopts micro-nano dual-scale corundum particles and WC to prepare aggregates for permeable bricks, which not only realizes the reuse of waste corundum and improves resource utilization, but also significantly enhances the strength and wear resistance of permeable bricks through in-situ synthesis technology and the formation of coherent interfaces, providing a more high-quality and durable building material choice for urban construction and environmental protection.
[0035] The TiO2 layer designed by the present invention has a lotus leaf-like structure, which has the following multiple effects: first, this unique structure gives the TiO2 layer excellent hydrophobic properties. The microstructure of the lotus leaf-like surface enables water droplets to quickly form a sphere when contacting the surface, thereby effectively reducing the contact area between water and the surface and achieving an efficient hydrophobic effect. This feature is crucial for permeable bricks because it can prevent moisture from accumulating on the surface of the brick body and keep the brick body dry and clean. Secondly, TiO2 itself has a photocatalytic effect and can decompose organic pollutants under light conditions to reduce environmental pollution. When the TiO2 layer is exposed to sunlight or other light sources, it can absorb light energy and generate photogenerated electrons and holes, which can react with oxygen and pollutants in water, thereby decomposing them into harmless substances. This photocatalytic effect not only helps to keep the permeable bricks clean, but also has a positive environmental protection effect on the surrounding environment. More importantly, the TiO2 layer of the present invention is on the surface of corundum, and the main component of corundum is A12O3. TiO2 is combined with A12O3 to form a semiconductor coupling structure, which can significantly improve the photocatalytic efficiency of TiO2. As a semiconductor material, the electrical conductivity of corundum complements that of TiO2, forming a more effective electron transmission channel. Under light conditions, corundum can quickly transfer photogenerated electrons to TiO2, promoting the progress of photocatalytic reactions. At the same time, the addition of corundum can also enhance the stability and durability of the TiO2 layer, enabling it to better cope with complex and changeable environmental conditions. In summary, the TiO2 layer designed by the present invention has the hydrophobic effect of the lotus leaf structure, the intrinsic photocatalytic effect of TiO2, and the semiconductor coupling structure formed by corundum and TiO2. These characteristics together give the permeable brick excellent self-cleaning performance. It can not only keep the brick body dry and clean, but also have a positive environmental protection effect on the surrounding environment, and has broad application prospects.
[0036] (3) Beneficial technical effects
[0037] Through a series of innovative designs, the present invention not only realizes the recycling of waste corundum and reduces environmental pollution, but also significantly improves the comprehensive performance of permeable bricks, bringing far-reaching impacts to urban construction and environmental protection. First, waste corundum is finely processed to make micro-nano dual-scale corundum particles. These particles play an important role at both the micro and nano scales: micro-scale particles provide a solid foundation strength for permeable bricks, while nano-scale particles fill the gaps between micro-scale particles, enhance interface bonding, and thus improve the strength and wear resistance of permeable bricks. In addition, through a reasonable particle assembly design, these corundum particles form a tight stacking structure, which significantly increases the density of permeable bricks and improves their overall performance such as compression resistance, flexural resistance, and freeze-thaw resistance. In order to further improve the performance of permeable bricks, a method for preparing permeable brick aggregates using WC and micro-nano dual-scale corundum particles is adopted. WC is tightly combined with corundum particles through in-situ synthesis technology, forming a strong binding force and a coherent interface. This interface structure enables the crystal structure of WC and corundum particles to match each other, greatly enhancing the interface bonding strength and further improving the strength and wear resistance of the permeable brick. This design not only realizes the reuse of waste corundum, but also provides a more high-quality and durable building material choice for urban construction and environmental protection. Finally, a TiO2 layer with a lotus leaf-like structure is designed on the surface of the permeable brick. This structure gives the TiO2 layer excellent hydrophobic properties, allowing water droplets to quickly form spheres when they contact the surface, effectively preventing moisture from accumulating on the surface of the brick body and keeping the brick body dry and clean. At the same time, the TiO2 layer itself has a photocatalytic effect, which can decompose organic pollutants under light conditions and reduce environmental pollution. More specifically, TiO2 combines with corundum (A12O3) to form a semiconductor coupling structure, which significantly improves the photocatalytic efficiency and enhances the stability and durability of the TiO2 layer. These characteristics together give the permeable brick excellent self-cleaning properties and have broad application prospects. In summary, the innovative design of the present invention realizes the recycling of waste corundum through synergy, reduces environmental pollution, and significantly improves the performance and life of permeable bricks. These innovative designs not only demonstrate strong environmental protection significance, but also provide strong support for urban construction and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the XRD spectrum of the phase analysis of the aggregate prepared in Example 1 of the present invention.
[0039] Figure 2 This is the XRD spectrum of the phase analysis of the permeable brick prepared in Example 1 of the present invention.
[0040] Figure 3 This is a scanning electron microscope (SEM) morphology image of the aggregate prepared in Example 1 of the present invention.
[0041] Figure 4This is a transmission electron microscope (TEM) morphology image of the aggregate prepared in Example 1 of the present invention.
[0042] Figure 5 This is a scanning electron microscope (SEM) morphology image of the TiO2 layer prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0043] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0044] In the absence of specific conditions, the operations in the examples are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. Parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0045] Reagents company Tetrabutyl titanate Guangzhou Haoyu International Trade Co., Ltd. Anhydrous ethanol Shanghai MacLean Biochemical Technology Co., Ltd. Acetic acid Shandong Mantanghong New Materials Co., Ltd. Polyvinyl alcohol Shanghai Yuanye Biotechnology Co., Ltd. Ammonium tungstate hydrate Jinan Jinhao Chemical Co., Ltd. glucose Shandong Mantanghong New Materials Co., Ltd. Sodium dodecylbenzenesulfonate Qianyan Chemical Technology (Wuhan) Co., Ltd. <![CDATA[SiO2]]> Shanghai Ruiyan Petrochemical Co., Ltd. Bentonite Sichuan Chengdu Hexinrunda Bentonite Mining Co., Ltd.
[0046] Example 1
[0047] A highly wear-resistant, self-cleaning ecological permeable brick, made of the following components by weight: 60 parts of aggregate, 4 parts of sintering aid, 2 parts of sodium dodecyl sulfate, 5 parts of water and 21 parts of titanium-containing precursor solution; the aggregate is spherical and consists of micro-nano dual-scale corundum particles and WC phase; the micro-nano dual-scale corundum particles consist of micron-scale corundum particles with a particle size of 4 μm and nano-scale corundum particles with a particle size of 30 nm;
[0048] The titanium-containing precursor solution is prepared from the following components in parts by weight: 4 parts of tetrabutyl titanate, 8 parts of anhydrous ethanol, 3 parts of acetic acid, 3 parts of polyvinyl alcohol and 3 parts of water.
[0049] The WC phase is formed by in-situ self-generation of a WC precursor solution at high temperature after drying; the WC precursor solution is prepared by the following components in parts by weight: 20 parts of ammonium tungstate hydrate, 8 parts of glucose, 2 parts of sodium dodecylbenzene sulfonate and 30 parts of water.
[0050] The interface between the above-mentioned micro-nano dual-scale corundum particles and the WC phase contains a coherent interface;
[0051] The sintering aid is a mixture of SiO2 and bentonite, and the mass ratio of SiO2 to bentonite is 1:1;
[0052] The porous surface of the highly wear-resistant and self-cleaning ecological permeable brick has a TiO2 layer with a lotus leaf structure; the TiO2 layer is synthesized at high temperature after the titanium precursor solution is dried;
[0053] The particle size of the above aggregate is 2 mm;
[0054] The volume percentage of the micron-scale corundum particles and the nano-scale corundum particles is 75%:25%; the volume percentage of the micro-nano dual-scale corundum particles and the WC phase is 55%:45%.
[0055] The present invention also provides a method for preparing a highly wear-resistant and self-cleaning ecological permeable brick, which comprises the following steps:
[0056] S1: preparing corundum particles: crushing, ball milling and sieving the waste corundum ceramics in sequence, and sieving out micron-scale corundum particles with a particle size of 4 μm and nano-scale corundum particles with a particle size of 30 nm for use;
[0057] S2: Preparation of WC precursor: By weight, 20 parts of ammonium tungstate hydrate, 8 parts of glucose, 4 parts of sodium dodecylbenzene sulfonate and 30 parts of water are mixed evenly.
[0058] S3: Preparation of aggregate: In terms of weight, 40 parts of micro-nano dual-scale corundum particles obtained in S1, 20 parts of WC precursor solution obtained in S2 and 3 parts of polyvinyl alcohol are mixed evenly to prepare a ceramic slurry, and then the aggregate blank is obtained by spray granulation, and then it is heat-treated at high temperature to obtain aggregate. The parameters of the spray granulation method are: the centrifugal frequency of the atomizing disk is 25, the inlet air temperature is 160°C, the outlet air temperature is 85°C, and the slurry inlet pressure is 40. The parameters of the heat treatment are: heat treatment in an argon atmosphere, the heat treatment temperature is 900°C, and the heat treatment time is 1h.
[0059] S4: Primary sintering of permeable bricks: 60 parts of aggregate, 4 parts of sintering aid, 2 parts of sodium dodecyl sulfate and 5 parts of water are mixed evenly, put into a mold and pressed to obtain a permeable brick blank, and then dried and sintered to obtain a pre-finished permeable brick. The parameters of the primary sintering are: sintering temperature of 1100℃ and sintering time of 4h under normal pressure and air atmosphere.
[0060] S5: Prepare a titanium-containing precursor solution for impregnation: mix 4 parts of tetrabutyl titanate and 8 parts of anhydrous ethanol to obtain a solution A for use, then mix 3 parts of acetic acid and 3 parts of water to obtain a solution B, and then drip the solution B into the solution A drop by drop to obtain a titanium-containing precursor solution for impregnation.
[0061] S6: Secondary sintering of permeable bricks: The pre-finished permeable bricks prepared in S4 are completely immersed in the titanium-containing precursor solution prepared in S5. After immersion for 5 minutes, the pre-finished permeable bricks are taken out and dried, and then subjected to secondary sintering to obtain highly wear-resistant and self-cleaning ecological permeable bricks. The parameters of the secondary sintering are: sintering temperature of 500°C and sintering time of 2 hours under normal pressure and nitrogen atmosphere.
[0062] Example 2
[0063] A highly wear-resistant, self-cleaning ecological permeable brick, made of the following components by weight: 75 parts of aggregate, 6 parts of sintering aid, 3 parts of sodium dodecyl sulfate, 6 parts of water and 28 parts of titanium-containing precursor solution; the aggregate is spherical and consists of micro-nano dual-scale corundum particles and WC phase; the micro-nano dual-scale corundum particles consist of micron-scale corundum particles with a particle size of 15 μm and nano-scale corundum particles with a particle size of 40 nm;
[0064] The titanium-containing precursor solution is prepared from the following components in parts by weight: 6 parts of tetrabutyl titanate, 9 parts of anhydrous ethanol, 4 parts of acetic acid, 4 parts of polyvinyl alcohol and 4 parts of water.
[0065] The WC phase is formed by in-situ self-generation of a WC precursor solution at high temperature after drying; the WC precursor solution is prepared by the following components in parts by weight: 30 parts of ammonium tungstate hydrate, 10 parts of glucose, 3 parts of sodium dodecylbenzene sulfonate and 35 parts of water.
[0066] The interface between the above-mentioned micro-nano dual-scale corundum particles and the WC phase contains a coherent interface;
[0067] The sintering aid is a mixture of SiO2 and bentonite, and the mass ratio of SiO2 to bentonite is 1:2;
[0068] The porous surface of the highly wear-resistant and self-cleaning ecological permeable brick has a TiO2 layer with a lotus leaf structure; the TiO2 layer is synthesized at high temperature after the titanium precursor solution is dried;
[0069] The particle size of the above aggregate is 4 mm;
[0070] The volume percentage of the micron-scale corundum particles and the nano-scale corundum particles is 78%:22%; the volume percentage of the micro-nano dual-scale corundum particles and the WC phase is 60%:40%.
[0071] The present invention also provides a method for preparing a highly wear-resistant and self-cleaning ecological permeable brick, which comprises the following steps:
[0072] S1: preparing corundum particles: crushing, ball milling and sieving the waste corundum ceramics in sequence, and sieving out micron-scale corundum particles with a particle size of 15 μm and nano-scale corundum particles with a particle size of 40 nm for use;
[0073] S2: Preparation of WC precursor: By weight, 30 parts of ammonium tungstate hydrate, 10 parts of glucose, 3 parts of sodium dodecylbenzene sulfonate and 35 parts of water are mixed evenly.
[0074] S3: Preparation of aggregate: In terms of weight, 45 parts of micro-nano dual-scale corundum particles obtained in S1, 25 parts of WC precursor solution obtained in S2 and 4 parts of polyvinyl alcohol are mixed evenly to prepare a ceramic slurry, and then the aggregate blank is obtained by spray granulation, and then it is heat-treated at high temperature to obtain aggregate. The parameters of the spray granulation method are: the centrifugal frequency of the atomizing disk is 30, the inlet temperature is 180°C, the outlet temperature is 90°C, and the slurry pressure is 45. The parameters of the heat treatment are: heat treatment in an argon atmosphere, the heat treatment temperature is 920°C, and the heat treatment time is 2h.
[0075] S4: Primary sintering of permeable bricks: 75 parts of aggregate, 6 parts of sintering aid, 3 parts of sodium dodecyl sulfate and 6 parts of water are mixed evenly, put into a mold and pressed to obtain a permeable brick blank, and then dried and primary sintered to obtain a pre-finished permeable brick. The parameters of the primary sintering are: sintering temperature of 1150℃ and sintering time of 5h at normal pressure and air atmosphere.
[0076] S5: Prepare a titanium-containing precursor solution for impregnation: mix 5 parts of tetrabutyl titanate and 9 parts of anhydrous ethanol to obtain a solution A for use, then mix 4 parts of acetic acid and 4 parts of water to obtain a solution B, and then drip the solution B into the solution A drop by drop to obtain a titanium-containing precursor solution for impregnation.
[0077] S6: Secondary sintering of permeable bricks: The pre-finished permeable bricks prepared in S4 are completely immersed in the titanium-containing precursor solution prepared in S5. After immersion for 6 minutes, the pre-finished permeable bricks are taken out and dried, and then subjected to secondary sintering to obtain highly wear-resistant and self-cleaning ecological permeable bricks. The parameters of the secondary sintering are: sintering temperature of 550°C and sintering time of 3 hours under normal pressure and nitrogen atmosphere.
[0078] Example 3
[0079] A highly wear-resistant, self-cleaning ecological permeable brick, made of the following components by weight: 90 parts of aggregate, 8 parts of sintering aid, 3 parts of sodium dodecyl sulfonate, 9 parts of water and 38 parts of titanium-containing precursor solution; the aggregate is spherical and consists of micro-nano dual-scale corundum particles and WC phase; the micro-nano dual-scale corundum particles consist of micron-scale corundum particles with a particle size of 40 μm and nano-scale corundum particles with a particle size of 70 nm;
[0080] The titanium-containing precursor solution is prepared from the following components in parts by weight: 8 parts of tetrabutyl titanate, 10 parts of anhydrous ethanol, 7 parts of acetic acid, 5 parts of polyvinyl alcohol and 6 parts of water.
[0081] The WC phase is formed by in-situ self-generation of a WC precursor solution at high temperature after drying; the WC precursor solution is prepared by the following components in parts by weight: 40 parts of ammonium tungstate hydrate, 12 parts of glucose, 3 parts of sodium dodecylbenzene sulfonate and 40 parts of water.
[0082] The interface between the above-mentioned micro-nano dual-scale corundum particles and the WC phase contains a coherent interface;
[0083] The sintering aid is a mixture of SiO2 and bentonite, and the mass ratio of SiO2 to bentonite is 1:2;
[0084] The porous surface of the highly wear-resistant and self-cleaning ecological permeable brick has a TiO2 layer with a lotus leaf structure; the TiO2 layer is synthesized at high temperature after the titanium precursor solution is dried;
[0085] The particle size of the above aggregate is 8 mm;
[0086] The volume percentage of the micron-scale corundum particles and the nano-scale corundum particles is 80%:20%; the volume percentage of the micro-nano dual-scale corundum particles and the WC phase is 70%:30%.
[0087] The present invention also provides a method for preparing a highly wear-resistant and self-cleaning ecological permeable brick, which comprises the following steps:
[0088] S1: preparing corundum particles: crushing, ball milling and sieving the waste corundum ceramics in sequence, and sieving out micron-scale corundum particles with a particle size of 40 μm and nano-scale corundum particles with a particle size of 80 nm for use;
[0089] S2: Preparation of WC precursor: by weight, 40 parts of ammonium tungstate hydrate, 12 parts of glucose, 7 parts of sodium dodecylbenzene sulfonate and 40 parts of water are mixed evenly.
[0090] S3: Preparation of aggregate: In terms of weight, 60 parts of micro-nano dual-scale corundum particles obtained in S1, 40 parts of WC precursor solution obtained in S2 and 7 parts of polyvinyl alcohol are mixed evenly to prepare a ceramic slurry, and then the aggregate blank is obtained by spray granulation, and then it is heat-treated at high temperature to obtain aggregate. The parameters of the spray granulation method are: the centrifugal frequency of the atomizing disk is 30, the inlet temperature is 190°C, the outlet temperature is 95°C, and the slurry inlet pressure is 55. The parameters of the heat treatment are: heat treatment in an argon atmosphere, the heat treatment temperature is 980°C, and the heat treatment time is 2h.
[0091] S4: Primary sintering of permeable bricks: 90 parts of aggregate, 8 parts of sintering aid, 3 parts of sodium dodecyl sulfate and 9 parts of water are mixed evenly, put into a mold and pressed to obtain a permeable brick blank, and then dried and primary sintered to obtain a pre-finished permeable brick. The parameters of the primary sintering are: sintering temperature of 1200℃ and sintering time of 7h at normal pressure and air atmosphere.
[0092] S5: Prepare a titanium-containing precursor solution for impregnation: mix 8 parts of tetrabutyl titanate and 10 parts of anhydrous ethanol to obtain a solution A for use, then mix 7 parts of acetic acid and 7 parts of water to obtain a solution B, and then drip the solution B into the solution A drop by drop to obtain a titanium-containing precursor solution for impregnation.
[0093] S6: Secondary sintering of permeable bricks: The pre-finished permeable bricks prepared in S4 are completely immersed in the titanium-containing precursor solution prepared in S5. After immersion for 8 minutes, the pre-finished permeable bricks are taken out and dried, and then subjected to secondary sintering to obtain highly wear-resistant and self-smelling ecological permeable bricks. The parameters of the secondary sintering are: sintering temperature of 580°C and sintering time of 4 hours under normal pressure and nitrogen atmosphere.
[0094] Example 4
[0095] A highly wear-resistant, self-cleaning, ecologically permeable brick, comprising the following components by weight: 95 parts of aggregate, 9 parts of sintering aid, 4 parts of sodium dodecyl sulfate, 10 parts of water, and 43 parts of a titanium-containing precursor solution; the aggregate is spherical and consists of micro-nano dual-scale corundum particles and a WC phase; the micro-nano dual-scale corundum particles consist of micron-scale corundum particles with a particle size of 45 μm and nano-scale corundum particles with a particle size of 90 nm;
[0096] The titanium-containing precursor solution is prepared from the following components in parts by weight: 9 parts of tetrabutyl titanate, 12 parts of anhydrous ethanol, 8 parts of acetic acid, 6 parts of polyvinyl alcohol and 8 parts of water.
[0097] The WC phase is formed by in-situ self-generation of a WC precursor solution at high temperature after drying; the WC precursor solution is prepared by the following components in parts by weight: 45 parts of ammonium tungstate hydrate, 15 parts of glucose, 4 parts of sodium dodecylbenzene sulfonate and 45 parts of water.
[0098] The interface between the above-mentioned micro-nano dual-scale corundum particles and the WC phase contains a coherent interface;
[0099] The sintering aid is a mixture of SiO2 and bentonite, and the mass ratio of SiO2 to bentonite is 1:3;
[0100] The porous surface of the highly wear-resistant and self-cleaning ecological permeable brick has a TiO2 layer with a lotus leaf structure; the TiO2 layer is synthesized at high temperature after the titanium precursor solution is dried;
[0101] The particle size of the above aggregate is 10 mm;
[0102] The volume percentage of the micron-scale corundum particles and the nano-scale corundum particles is 85%:15%; the volume percentage of the micro-nano dual-scale corundum particles and the WC phase is 75%:25%.
[0103] The present invention also provides a method for preparing a highly wear-resistant and self-cleaning ecological permeable brick, which comprises the following steps:
[0104] S1: preparing corundum particles: crushing, ball milling and sieving the waste corundum ceramics in sequence, and sieving out micron-scale corundum particles with a particle size of 45 μm and nano-scale corundum particles with a particle size of 90 nm for use;
[0105] S2: Preparation of WC precursor: By weight, 45 parts of ammonium tungstate hydrate, 15 parts of glucose, 8 parts of sodium dodecylbenzene sulfonate and 45 parts of water are mixed evenly.
[0106] S3: Preparation of aggregate: In terms of weight, 65 parts of micro-nano dual-scale corundum particles obtained in S1, 45 parts of WC precursor solution obtained in S2 and 8 parts of polyvinyl alcohol were mixed evenly to prepare a ceramic slurry, and then the aggregate blank was obtained by spray granulation, and then the aggregate was heat-treated at high temperature to obtain the aggregate. The parameters of the spray granulation method are: the centrifugal frequency of the atomizing disk is 35, the inlet temperature is 210°C, the outlet temperature is 100°C, and the slurry pressure is 60. The parameters of the heat treatment are: heat treatment in an argon atmosphere, the heat treatment temperature is 1000°C, and the heat treatment time is 3h.
[0107] S4: Primary sintering of permeable bricks: 95 parts of aggregate, 9 parts of sintering aid, 4 parts of sodium dodecyl sulfate and 10 parts of water are mixed evenly, put into a mold and pressed to obtain a permeable brick blank, and then dried and primary sintered to obtain a pre-finished permeable brick. The parameters of the primary sintering are: sintering temperature of 1250℃ and sintering time of 8h under normal pressure and air atmosphere.
[0108] S5: Prepare a titanium-containing precursor solution for impregnation: mix 9 parts of tetrabutyl titanate and 12 parts of anhydrous ethanol to obtain a solution A for use, then mix 8 parts of acetic acid and 8 parts of water to obtain a solution B, and then drip the solution B into the solution A drop by drop to obtain a titanium-containing precursor solution for impregnation.
[0109] S6: Secondary sintering of permeable bricks: The pre-finished permeable bricks prepared in S4 are completely immersed in the titanium-containing precursor solution prepared in S5. After immersion for 10 minutes, the pre-finished permeable bricks are taken out and dried, and then subjected to secondary sintering to obtain highly wear-resistant and self-cleaning ecological permeable bricks. The parameters of the secondary sintering are: sintering temperature of 600°C and sintering time of 5 hours under normal pressure and nitrogen atmosphere.
[0110] Example 5
[0111] The method is basically the same as Example 1, except that the micro-nano dual-scale corundum particles used to prepare the aggregate are composed of micron-scale corundum particles with a particle size of 45 μm and nano-scale corundum particles with a particle size of 90 nm.
[0112] Comparative Example 1
[0113] The method is basically the same as Example 1, except that acetic acid and polyvinyl alcohol are not added in the preparation of the titanium-containing precursor solution, so the TiO2 layer does not form a lotus leaf-like structure.
[0114] Comparative Example 2
[0115] The method is substantially the same as Example 1, except that the micro-corundum particles used to prepare the aggregate are composed of micron-scale corundum particles of a single size of 4 μm.
[0116] Comparative Example 3
[0117] The method is basically the same as Example 1, except that the micro-corundum particles used to prepare the aggregate are composed of single-sized nano-scale corundum particles of 30 nm.
[0118] Needle test:
[0119] Scanning electron microscopy (SEM): Use scanning electron microscopy to observe and characterize the morphological characteristics of aggregates, such as particle shape, size, surface structure, etc. X-ray diffraction (XRD): Use an X-ray diffractometer to characterize the physical phase of permeable bricks, that is, to determine its composition and structure by analyzing the crystal structure and lattice parameters in the sample. Transmission electron microscopy (TEM): Use a transmission electron microscope to observe and characterize the interface characteristics between corundum particles and WC (tungsten carbide), such as interface bonding conditions, interactions, etc.
[0120] Figure 1 The XRD spectrum of the phase analysis of the aggregate prepared in Example 1 of the present invention, from which it can be clearly seen that corundum and WC phases exist; Figure 2 The XRD spectrum of the phase analysis of the permeable brick prepared in Example 1 of the present invention shows that in addition to the corundum and WC phases, there are also bentonite and TiO2 phases; Figure 3 The SEM morphology of the aggregate prepared in Example 1 of the present invention clearly shows the presence of micron-scale corundum and nano-scale corundum particles; Figure 4 This is a transmission electron microscope TEM morphology image of the aggregate prepared in Example 1 of the present invention, from which the coherent interface between corundum and WC can be clearly seen; Figure 5 This is a scanning electron microscope (SEM) morphology image of the TiO2 layer prepared in Example 1 of the present invention. It can be clearly seen from the image that the TiO2 layer has a structure that imitates the surface morphology of a lotus leaf.
[0121] Performance Test:
[0122] Compressive strength: When evaluating the compressive strength of permeable bricks, the relevant regulations and requirements of the national standard GB / T25993-2010 are strictly followed. These standards ensure the accuracy and reliability of the compressive strength test and provide strong guarantees for practical applications.
[0123] Splitting tensile strength: refer to the splitting tensile strength test method of GB / T 25993-2010.
[0124] Water permeability: When evaluating the water permeability of permeable bricks, the water permeability coefficient is used as the key indicator, and the test is carried out in strict accordance with the requirements of the national standard GB / T 25993-2010. This standard provides standardized test methods and clear evaluation criteria to ensure that the water permeability of permeable bricks can be accurately and reliably evaluated.
[0125] Wear resistance: Evaluate according to the grinding pit length measurement method in GB / T 12988 standard to accurately measure the performance of permeable bricks after friction and wear.
[0126] Easy to clean: In order to evaluate the easy to clean of permeable bricks, the test was conducted with reference to GB / T31859-2015. A specific unit of characterization, A, is required to indicate the amount of oil residue per unit area. Based on the test results, the following easy to clean classification standards were formulated: When the A value is less than or equal to 0.50g / m 2 When the A value is 0.50g / m 2 Up to 1.00g / m 2 When the A value is between 1.00 g / m 2 Up to 1.5g / m 2 When the A value is greater than 1.5 g / m 2 When the permeable brick is cleaned, it is considered to be uncleanable, indicating that the oil residue on its surface is serious and difficult to remove by conventional cleaning methods. This test method allows us to accurately evaluate the easy-to-clean performance of different permeable bricks, providing more practical and environmentally friendly options for urban construction and landscape design.
[0127] Antibacterial performance: The test was conducted in accordance with the JC / T897-2014 standard. The core goal of this test is to verify the antibacterial effect of ceramic glaze on Escherichia coli AS1.90 and Staphylococcus aureus AS1.89.
[0128] The performances of the permeable bricks of Examples 1 to 5 and Comparative Examples 1 to 3 are summarized in Table 2.
[0129] Table 2 Performance of permeable bricks in Examples 1 to 5 and Comparative Examples 1 to 3
[0130]
[0131]
[0132] The main difference between Comparative Example 1 and Example 1 is whether the TiO2 layer inside the permeable brick has a lotus leaf structure. From Table 2, it can be seen that the formation of a lotus leaf structure on the TiO2 layer inside the permeable brick can significantly improve the cleanability and antibacterial rate of the permeable brick, thereby increasing the self-cleaning property of the permeable brick.
[0133] The main difference between Comparative Example 2 and Example 1 is whether the aggregate is prepared from micro-nano corundum particles. From Table 2, it can be seen that the permeable bricks prepared from corundum particles composed of single-sized micron-scale corundum particles have significantly lower wear resistance, compressive strength and splitting tensile strength than the permeable bricks prepared from micro-nano-scale mixed corundum particles.
[0134] The main difference between Comparative Example 3 and Example 1 is whether the aggregate is prepared from micro-nano corundum particles. From Table 2, it can be seen that the permeable bricks prepared from corundum particles composed of nanoscale corundum particles of a single size are significantly lower in wear resistance, compressive strength and splitting tensile strength than the permeable bricks prepared from micro-nanoscale mixed corundum particles.
[0135] In summary, the present invention realizes the recycling of waste corundum, reduces environmental pollution, and greatly improves the performance of permeable bricks through innovative design. Waste corundum is finely processed into micro-nano particles, which enhances the strength and wear resistance of permeable bricks. At the same time, the performance of the bricks is further improved by combining WC with corundum particles. In addition, the TiO2 layer designed on the surface of the permeable brick has excellent hydrophobicity and photocatalysis, which can effectively self-disperse and keep dry and clean. These innovations not only contribute to urban construction, but also show significant environmental significance, opening up new prospects for the widespread application of permeable bricks.
[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A highly wear-resistant, self-cleaning, ecologically permeable brick, made from the following components by weight: 60-95 parts of aggregate, 4-9 parts of sintering aid, 2-4 parts of sodium dodecyl sulfate, 5-10 parts of water and 21-43 parts of titanium-containing precursor solution; The aggregate is spherical and consists of micro-nano dual-scale corundum particles and WC phase; The micro-nano dual-scale corundum particles are composed of micron-scale corundum particles with a particle size of 4-45 μm and nano-scale corundum particles with a particle size of 30-90 nm; The titanium-containing precursor solution is prepared from the following components in parts by weight: 4 to 9 parts of tetrabutyl titanate, 8 to 12 parts of anhydrous ethanol, 3 to 8 parts of acetic acid, 3 to 6 parts of polyvinyl alcohol and 3 to 8 parts of water; The WC phase is formed in situ at high temperature after the WC precursor solution is dried; The WC precursor solution is prepared by the following components in parts by weight: 20-45 parts of ammonium tungstate hydrate, 8-15 parts of glucose, 2-4 parts of sodium dodecylbenzene sulfonate and 30-45 parts of water; The interface between the micro-nano dual-scale corundum particles and the WC phase contains a coherent interface; The sintering aid is a mixture of SiO2 and bentonite, the mass ratio of SiO2 and bentonite is 1: (1 ~ 3); The porous surface inside the highly wear-resistant self-cleaning ecological permeable brick has a TiO2 layer with a lotus leaf structure; The TiO2 layer is synthesized at high temperature after a titanium-containing precursor solution is dried.
2. A highly wear-resistant and self-cleaning ecological permeable brick as claimed in claim 1, characterized in that: The particle size of the aggregate is 2-10 mm.
3. The highly wear-resistant and self-cleaning ecological permeable brick according to claim 1, characterized in that: The volume percentage of the micron-scale corundum particles and the nano-scale corundum particles is (75-85%): (15-25%).
4. The highly wear-resistant and self-cleaning ecological permeable brick according to claim 1, characterized in that: The volume percentage of the micro-nano dual-scale corundum particles and the WC phase is (55-75%): (25-45%).
5. A method for preparing a highly wear-resistant and self-cleaning ecological permeable brick according to any one of claims 1 to 4, comprising the following steps: S1: preparing corundum particles: crushing, ball milling and screening the waste corundum ceramics in turn to screen out micron-scale corundum particles with a particle size of 4-45 μm and nano-scale corundum particles with a particle size of 30-90 nm for use; S2: Preparation of WC precursor: by weight, 20-45 parts of ammonium tungstate hydrate, 8-15 parts of glucose, 4-8 parts of sodium dodecylbenzene sulfonate and 30-45 parts of water are mixed evenly; S3: preparing aggregate: by weight, 40-65 parts of the micro-nano dual-scale corundum particles obtained in S1, 20-45 parts of the WC precursor solution obtained in S2 and 3-8 parts of polyvinyl alcohol are mixed evenly to prepare a ceramic slurry, and then an aggregate blank is obtained by a spray granulation method, which is then heat-treated at a high temperature to obtain an aggregate; S4: Primary sintering of permeable bricks: 60-95 parts of aggregate, 4-9 parts of sintering aid, 2-4 parts of sodium dodecyl sulfate and 5-10 parts of water are mixed evenly, put into a mold and pressed to obtain a permeable brick blank, and after drying, the primary sintering is performed to obtain a pre-finished permeable brick; S5: preparing a titanium-containing precursor solution for impregnation: uniformly mixing 4-9 parts of tetrabutyl titanate and 8-12 parts of anhydrous ethanol to obtain a solution A for standby use, and then uniformly mixing 3-8 parts of acetic acid and 3-8 parts of water to obtain a solution B, and then dripping the solution B into the solution A drop by drop, and obtaining a titanium-containing precursor solution for impregnation after dripping; S6: Secondary sintering of permeable bricks: The permeable brick pre-finished product prepared in S4 is completely immersed in the titanium-containing precursor solution prepared in S5. After immersion for 5 to 10 minutes, the permeable brick pre-finished product is taken out and dried, and then subjected to secondary sintering to finally obtain a highly wear-resistant and self-cleaning ecological permeable brick.
6. The method for preparing a highly wear-resistant and self-cleaning ecological permeable brick according to claim 5, characterized in that: The parameters of the heat treatment in step S3 are: heat treatment is performed in an argon atmosphere, the heat treatment temperature is 900-1000° C., and the heat treatment time is 1-3 hours.
7. The method for preparing a highly wear-resistant and self-cleaning ecological permeable brick according to claim 5, characterized in that: The parameters of the initial sintering in step S4 are: sintering temperature of 1100-1250° C. and sintering time of 4-8 hours in normal pressure and air atmosphere.
8. The method for preparing a highly wear-resistant and self-cleaning ecological permeable brick according to claim 5, characterized in that: The parameters of the secondary sintering in step S6 are: under normal pressure and in a nitrogen atmosphere, the sintering temperature is 500-600° C., and the sintering time is 2-5 hours.
Citation Information
Patent Citations
Directional porous SiC and diamond reinforced Al base composite material and preparation method thereof
CN104962771A
Self-cleaning ecological permeable brick and preparation method thereof
CN106242618A